"Funding does something to people": NGOs navigating funding challenges in India. Issue 1 (2nd January 2022) - Mount, Liz
ABSTRACT: This article offers an ethnographic exploration of NGO "mission creep" as a result of obtaining funding. Many scholars express scepticism about funding on NGO goals, while others encourage a nuanced critique. This 18-month ethnographic study of two NGOs in Bangalore, India, explores NGO workers navigating the acceptance of funding while maintaining their original missions. When one NGO failed to uphold this goal, staff members created their own NGO. Findings indicate that even when NGO staff have experienced mission creep from funding and make conscious efforts to maintain their missions, they face structural barriers that make this difficult and perhaps impossible.